Pendampingan Pembuatan Imooji sebagai Media Promosi Digital bagi Usaha Kecil di Kota Banjarmasin - Muhammad Rahmattullah; Jumariati Jumariati; Syaripudin Bahar; Nanda Factur Risa; Muhammad Andrian; Muhammad Arda Bily; Risnande Dwi Soraya (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Imooji is a digital promotional media to introduce products or services from small businesses that are not widely known. The introduction of small businesses to digital promotional media is very important, especially during a pandemic, in order to overcome the constraints of direct promotion which has limited activities. This program aims to provide assistance to a number of small businesses in utilizing Imooji as part of the development of the creative economy. The scope of this program includes 20 small businesses in Banjarmasin. The method of this program is through direct assistance to each place of business with the involvement of lecturers and student groups as companions. This program has an impact on increasing the knowledge of small business actors about Imooji as a form of promotional media. They are also directly assisted in creating Imooji to promote their business digitally. The result of the program is an increase in the skills of small business actors in making Imooji as a digital promotion medium for their business. The digital literacy of the small business actors involved is also increasing and hoped that will help them to promote their business efficiently and effectively.